TWEED Code Book - Engene, Jan Oskar (The University of Bergen, 2006)
The TWEED data set contains information on more than 11.000 events related to internal (or domestic) terrorism in 18 West European countries for the 1950 through 2004 period. The code book describes the structure of the data set, the countries covered, and the variables included and functions as a user’s guide to the data set. The data set is available at: http://www.uib.no/people/sspje/tweed.htm The data set Terrorism in Western Europe: Events Data, TWEED, contains information on events related to internal (or domestic) terrorism in 18 West European countries (Austria, Belgium, Denmark, Finland, France, Germany, Greece, Iceland, Ireland, Italy, Luxembourg, the Netherlands, Norway, Portugal, Spain, Sweden, Switzerland, and the United Kingdom of Great Britain and Northern Ireland). By limiting itself to internal terrorism, the TWEED data set only includes events initiated by agents originating in the West European countries. In the TWEED data set, data has been collected for the period from 1950 to 2004. In total, 11.026 events are recorded in the TWEED data set. Of these, 9542 events (86.5%) are actions initiated by terrorist groups or non-state agents. The remaining events are government actions directed mainly against terrorists. The total number of deaths resulting from actions by terrorist agents recorded in the TWEED data set is 2959. The data set records activities by around 200 terrorist groups identified by name. The code book documents the structure of the data set and the variables included in it.